Engineering design and performance evaluation of a transmission system for the UG 24 urban energy vehicle - Muhammad Farid Riyanto; Juni Noor Rohman; Sutiman (Universitas Negeri Yogyakarta, 2025)
The development of energy-efficient vehicles in student competitions encourages innovation in lightweight and high-performance automotive systems. The Garuda UNY Team, representing Universitas Negeri Yogyakarta, has been actively involved in national competitions such as the Kontes Mobil Hemat Energi (KMHE). In recent evaluations, the team identified a critical weakness in their vehicle's drivetrain, specifically the Internal Gear Hub (IGH) used in the UG-24, which failed to withstand engine torque during acceleration, leading to gear slippage and mechanical failure. To address this issue, a new transmission system was designed and manufactured using the 4D development framework: Define, Design, Develop, and Disseminate. The Define phase identified the mismatch between the IGH design and engine torque requirements. In the Design phase, a new gearbox layout was modeled using Autodesk Inventor, incorporating components such as a crankcase, cover, and custom gear ratios. The development phase involved selecting materials, laser cutting, machining, and assembling transmission parts from mild steel and aluminum. Finally, the Dissemination phase consisted of installing the system in the UG-24 vehicle and conducting a performance evaluation through structured interviews with drivers. Evaluation results showed improved gear shifting performance, with a 75% success rate across ten indicators. Despite positive outcomes, some issues, such as shifting resistance and gear engagement noise, were observed. These were linked to cable friction and dog clutch geometry. Design improvements such as optimized routing and chamfering were recommended for future iterations. This research highlights the impact of tailored transmission systems in student-built energy-efficient vehicles. It provides insight into practical, scalable drivetrain solutions.